2016
DOI: 10.4236/health.2016.86058
|View full text |Cite
|
Sign up to set email alerts
|

Pain-Related Knowledge and Barriers among Jordanian Nurses: A National Study

Abstract: The purpose of this study is to explore Jordanian nurses' knowledge and attitudes regarding pain assessment, and barriers to intervention at different hospitals representing health care sectors in Jordan. A descriptive cross-sectional design was used in this study utilizing self-administered questionnaires to collect data from nurses working in public, University-affiliated, and private hospitals located on the north, mid, and south of Jordan using Nurses' Knowledge and Attitudes Survey Regarding Pain, (n = 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 40 publications
5
24
1
Order By: Relevance
“…In Jordan, like many countries, there is a growing interest in pain management. Scholars are focusing on pain‐related issues in patients with cancer, critical illness, and surgery (D'emeh, Yacoub, Darawad, Al‐Badawi, & Shahwan, ; Shoqirat, ). However, there is little attention on pain experienced in the ED.…”
Section: Introductionmentioning
confidence: 99%
“…In Jordan, like many countries, there is a growing interest in pain management. Scholars are focusing on pain‐related issues in patients with cancer, critical illness, and surgery (D'emeh, Yacoub, Darawad, Al‐Badawi, & Shahwan, ; Shoqirat, ). However, there is little attention on pain experienced in the ED.…”
Section: Introductionmentioning
confidence: 99%
“…The participating nurses and nurse managers articulated diverse preferences on the nature of the educational programme based on their personal choices and working dynamics. They indicated a willingness to learn from an experienced person or group of persons provided they possessed the requisite knowledge and expertise in both the subject content and the pedagogical approaches (D’emeh, Yacoub, Darawad, Al‐Badawi, & Shahwan, ). In general, a face‐to‐face interactive educational session with a group were most often identified as preferable.…”
Section: Discussionmentioning
confidence: 99%
“…In Jordan, the role of nurses in pain management is to fulfill physicians' orders without any guidelines. 8 A previous study result demonstrated knowledge deficit and attitude; nurses underestimated and undertreated patients' pain. Research on palliative care topics are limited.…”
Section: Palliative Education and Researchmentioning
confidence: 94%
“…16 Jordanian nurses work with patients among which 97% of population are Muslims and they believe that suffering is a test from God and a person should tolerate his/her pain and hide it from others. 8 Moreover, traditional Muslims respond well to euphemisms which mean represent the truth in a different way that can be accepted. 16 Most are seeking reassurance and empathy rather than information about diagnosis.…”
Section: Cultural Beliefsmentioning
confidence: 99%
See 1 more Smart Citation